Implementation of the economic competence principle in the training of a modern specialist - Sergeeva, M. G.; Stepanyan, T. M.; Latysheva, N. A.; Tumanov, E. V.; Solovyov, B. A.; Parinov, D. V.; Nedova, N. S. (Revista de la Universidad del Zulia, 2019)
Systemic changes have been initiated in Russian education aimed at ensuring its compliance with both the requirements of the innovative economy and the needs of society. At the same time, the priority directions in this sphere are to bring the content and structure of professional training in accordance with the modern needs of the labor market and increase the availability of quality educational services. In modern conditions, the concept of continuing professional education should be considered as an instrument of economic policy aimed at increasing competitiveness, achieving fuller employment, ensuring professional mobility of employees in connection with the implementation of new technologies. Research results. Based on the well-known principles of continuing education, the authors define the principle of economic competence based on the requirements of the market economy for the training of competitive specialists. The definition of economic competence of a graduate of a professional educational institution is based on the concepts of “competence”, “competency”, “professional competence”. In identifying the essence of economic competence, the authors proceeded from the categories “activity”, “professional activity”, “economic activity” and “labor activity”. Discussion. As a result of the study, the authors identified the levels of continuous economic education in the system of vocational education (basic, professional, additional), which allow students after completing training at a certain level to perform the necessary labor actions and hold the appropriate positions. Conclusion. The article proves the necessity of realization of the justified principle of economic competence, which establishes the relationship between knowledge as information and knowledge as an activity in the preparation of practice-oriented specialists for the market economy, enriching the modern didactics of lifelong education.